2018
DOI: 10.1111/vox.12713
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the tube test and column agglutination techniques for anti‐A/‐B antibody titration in healthy individuals

Abstract: Background and Objectives Determination of the anti-A/-B titre pre-and posttransplantation is beneficial for treatment selection. Currently, the recommended method for antibody titration is the tube test (TT) assay. Dithiothreitol (DTT) is used for IgM antibody inactivation. Recently, a fully automated antibody titration assay using the column agglutination technique (CAT) was developed (auto-CAT). Our aim was to compare the auto-CAT and TT techniques for ABO antibody titration, to evaluate the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
5
14
2
Order By: Relevance
“…There are very few publications available in support of whether DTT can be used in CAT or whether DTT treatment of serum (or plasma) leads to falsepositive reactions by CAT. 10 As cases of ABO-incompatible transplants are gradually increasing in resource-constrained developing countries across the globe, it has become extremely important for immunohematology laboratories to validate an accurate method to estimate precise IgM and IgG levels of reactivity in ABO titers in patients as well as in potential healthy organ or stem cell donors.…”
mentioning
confidence: 99%
“…There are very few publications available in support of whether DTT can be used in CAT or whether DTT treatment of serum (or plasma) leads to falsepositive reactions by CAT. 10 As cases of ABO-incompatible transplants are gradually increasing in resource-constrained developing countries across the globe, it has become extremely important for immunohematology laboratories to validate an accurate method to estimate precise IgM and IgG levels of reactivity in ABO titers in patients as well as in potential healthy organ or stem cell donors.…”
mentioning
confidence: 99%
“…Bhangle et al compared CTT with CAT for anti-A and anti-B titre estimation using 67 samples and concluded that CAT results are more sensitive than CTT [29]. Likewise, Matsura et al compared the titration by CTT with CAT using 30 samples and concluded that 1+ agglutination using the CTT technique is equivalent to weak agglutination obtained by the automated CAT [30]. They recommended that DTT may be used with automated CAT to measure antibody titres.…”
Section: Discussionmentioning
confidence: 99%
“…The level of ABO antibody is predominantly determined with plasma dilutions tested by either manual serology in tubes, or automated or semiautomated in cassettes (CAT) with both observing IgM direct agglutination and using antiglobulin reagents to detect IgG. We observed apparent differences in determination of antibody levels in both donors and patients, depending on the technology used.…”
Section: Discussionmentioning
confidence: 99%